2010
DOI: 10.1007/s10530-009-9683-1
|View full text |Cite
|
Sign up to set email alerts
|

Alien plant species favoured over congeneric natives under experimental climate warming in temperate Belgian climate

Abstract: Climate warming and biological invasions by alien species are two key factors threatening the world's biodiversity. To date, their impact has largely been studied independently, and knowledge on whether climate warming will promote invasions relies strongly on bioclimatic models. We therefore set up a study to experimentally compare responses to warming in native and alien plant species. Ten congeneric species pairs were exposed to ambient and elevated temperature (?3°C) in sunlit, climatecontrolled chambers, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
33
2
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 58 publications
6
33
2
2
Order By: Relevance
“…This contrasts with the positive responses of introduced species to increased temperatures observed elsewhere (e.g. Verlinden & Nijs ; Chuine et al . ; He, Li & Peng ; Liu et al .…”
Section: Discussioncontrasting
confidence: 93%
“…This contrasts with the positive responses of introduced species to increased temperatures observed elsewhere (e.g. Verlinden & Nijs ; Chuine et al . ; He, Li & Peng ; Liu et al .…”
Section: Discussioncontrasting
confidence: 93%
“…In this experiment, the day- and night-warming might induce the occurrence of photosynthetic overcompensation in E. adenophorum , while the daily-warming did not yield such an effect. Verlinden & Nijs (2010) found that invasive plants showed no response to daily-warming [15]. This is consistent with our findings.…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, we also found a similar trait–environment interaction in our model of native species distribution (Figure ). But in addition, warmer conditions provided a specific advantage to alien species over most native species in these grasslands (Verlinden & Nijs, ), because natives on average did not respond as positively to GDD as did alien species (Figure ). This has interesting implications for the future of invasions in grasslands under predicted scenarios of climate change (Bradley et al, ), because alien species will be on average more favoured than natives by a rapidly warming climate, particularly in climatically harsh environments, such as mountain ranges (Carboni et al, ).…”
Section: Discussionmentioning
confidence: 99%